2017
DOI: 10.1002/aenm.201700294
|View full text |Cite
|
Sign up to set email alerts
|

A Lithium Amide‐Borohydride Solid‐State Electrolyte with Lithium‐Ion Conductivities Comparable to Liquid Electrolytes

Abstract: storage materials. [4] As SSEs for lithiumion batteries, they offer multiple advantages including the natural abundance of their constituent elements, their light weight, negligible electronic conduction, and low grain boundary resistance. [5] The prototypical example is LiBH 4 , whose Li + conductivity increases abruptly to >1 × 10 −3 S cm −1 above 100 °C due to a structural phase transition. [6] This superionic high-temperature phase can be stabilized at room temperature by incorporation of lithium halides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
96
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 36 publications
4
96
0
Order By: Relevance
“…batteries which exclude flammable organic liquid electrolytes are considered as one of the most promising solutions. [5][6][7][8][9][10][11][12] Despite the poor chemical stability (e.g., instability in atmospheric air and conventional polar solvents), sulfide solid electrolyte (SE) materials are highly promising to realize all-solid-state Li-ion or Li batteries (ASLBs) which may outperform conventional LIBs. [5,[13][14][15][16][17][18][19][20][21] Li + conductivities of several state-of-the-art sulfide Li + superionic conductors have reached ≈10 −2 S cm −1 at room temperature (Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 [13] : 2.5 × 10 −2 S cm −1 , Li 7 P 3 S 11 [22] : 1.7 × 10 −2 S cm −1 ), which is comparable to that of organic liquid electrolytes.…”
Section: Doi: 101002/aenm201802927mentioning
confidence: 99%
“…batteries which exclude flammable organic liquid electrolytes are considered as one of the most promising solutions. [5][6][7][8][9][10][11][12] Despite the poor chemical stability (e.g., instability in atmospheric air and conventional polar solvents), sulfide solid electrolyte (SE) materials are highly promising to realize all-solid-state Li-ion or Li batteries (ASLBs) which may outperform conventional LIBs. [5,[13][14][15][16][17][18][19][20][21] Li + conductivities of several state-of-the-art sulfide Li + superionic conductors have reached ≈10 −2 S cm −1 at room temperature (Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 [13] : 2.5 × 10 −2 S cm −1 , Li 7 P 3 S 11 [22] : 1.7 × 10 −2 S cm −1 ), which is comparable to that of organic liquid electrolytes.…”
Section: Doi: 101002/aenm201802927mentioning
confidence: 99%
“…Density functional theory (DFT) calculations combined with quasielastic neutron scattering (QENS) characterization indicated that more lithium defects were created upon doping with LiI, and high concentration of Frenkel pair could mainly contribute to the improved ionic conductivity . Partially replacing [BH 4 − ] with [NH 2 ] − or [NH] 2‐ in LiBH 4 will also enhance Li ion mobility. Thanks to the new occupation sites for Li + ions in the phases or metastable state of Li 2 (BH 4 )(NH 2 ), Li 4 (BH 4 )(NH 2 ) 2 and Li 4 (BH 4 )(NH 2 ) 3 ionic conductivities of four orders of magnitude higher than that of neat LiBH 4 can be achieved at room temperature .…”
Section: Complex Hydrides As Solid‐state Electrolytementioning
confidence: 99%
“…Partially replacing [BH 4 − ] with [NH 2 ] − or [NH] 2‐ in LiBH 4 will also enhance Li ion mobility. Thanks to the new occupation sites for Li + ions in the phases or metastable state of Li 2 (BH 4 )(NH 2 ), Li 4 (BH 4 )(NH 2 ) 2 and Li 4 (BH 4 )(NH 2 ) 3 ionic conductivities of four orders of magnitude higher than that of neat LiBH 4 can be achieved at room temperature . DFT calculations revealed that the Li + hopping from the filled sublattice into empty sublattice followed by Li + shuttling between empty sublattice.…”
Section: Complex Hydrides As Solid‐state Electrolytementioning
confidence: 99%
“…In addition, the Li(BH 4 ) 1− x (NH 2 ) x ( x = 2/3) compound presented a preserved cubic α phase with a slightly increased lattice parameter (10.670 Å) compared to the cubic Li(BH 4 ) 1− x (NH 2 ) x ( x = 3/4) (10.655 Å) reported in the literature . A small peak at 2θ ≈ 25°–30° (marked by a star) was observed in the x = 2/3 phase (Figure h), which could be ascribed to a previously reported metastable γ phase within the amide–borohydride phase diagram . These peaks were absent in the patterns of the x = 3/4 phase.…”
Section: Progress Of Borohydride‐based Solid‐state Electrolytes and Amentioning
confidence: 62%
“…In the fcc lattices with only edge‐ and corner‐sharing tetrahedral sites, Li ions are found to migrate along the intermediate octahedral sites . After mapping the cubic α phase of lithium amide–borohydrides to a distorted fcc lattice, to accommodate the fast reorientation of highly polarized NH 2 − groups, a different, yet less‐energy‐demanding, migration within two edge‐sharing tetrahedral sites is adopted, which enables improved lithium‐ion hopping and high ionic conductivity of the lithium amide–borohydride compound . The sulfides generally exhibit faster Li + ‐ion diffusion .…”
Section: Progress Of Borohydride‐based Solid‐state Electrolytes and Amentioning
confidence: 99%